ON ORAL ATTAINMENT IN A FOREIGN LANGUAGE - Pospieszyńska-Wojtkowiak, Magdalena (Scripta Neophilologica Posnaniensia, 2019)
The article is devoted to oral attainment in a foreign language. It revises the term speaking, and explains its difficult role, yet fundamental both in teaching and in learning. Although oral communication is not easy to success in, it is, inevitably, one of the main determinants of students’ achievements in a classroom situation. The article presents what happens during a typical classroom interaction situation, emphasizing the cooperation between the speaker and the listener, quoting Grice’s (1975) four maxims governing the cooperation in communication, namely, the maxim of quantity, quality, relation and manner. Then, various features, factors and functions related to speaking are enumerated, underlining the difficult role of speaking in the whole process of foreign language learning. According to Common European Framework (Council of Europe 2001), all the features of spoken language, also mediating and interaction, are important in designing speaking tasks/tests, setting the assessment criteria, establishing and organizing principles and curricula for the teaching programs. The last section of the article is devoted to assessing oral skills, hence different approaches and scales are presented as examples, together with a brief explanation of the constructs of reliability and validity is speaking assessment. Special reliability and validity procedures have to be employed by test designers in order to obtain objectivity of the scores.